Implementation Analysis of Improvement of Building Use Rights to Property Rights for Residential Houses - Avianita Febriana Yulianto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this research is to analyze and find out: 1) Implementation of upgrading the status of building use rights to property rights for residential houses at the Cilacap Regency Land Office. 2). Obstacles and solutions in the implementation of increasing the status of Building Use Rights to Property Rights for residential houses at the Cilacap Regency Land Office, namely Petitioners who will register for an increase in land rights for residential houses often do not include an application file with a Building Permit, the public does not know about procedures and conditions that must be attached at the time of submitting an application. To overcome the above constraints, the Cilacap Regency Land Office conducted socialization, this aims to understand information and to straighten people's perceptions who think that upgrading the status of Building Use Rights to Property Rights for residential houses is too complicated and expensive. 2) Obstacles and solutions in the implementation of increasing the status of Building Use Rights to Property Rights for residential houses at the Cilacap Regency Land Office, namely Petitioners who will register for an increase in land rights for residential houses often do not include an application file with a Building Permit, the public does not know about procedures and conditions that must be attached at the time of submitting an application. To overcome the above constraints, the Cilacap Regency Land Office conducted socialization, this aims to understand information and to straighten out public perceptions who consider that upgrading the status of Building Use Rights to Property Rights for residential houses is too complicated and expensive.